ORTHODONTIC TREATMENT NEEDS IN STUDENTS 12-15 YEARS USING ORTHODONTIC TREATMENT NEEDS INDICATOR (IKPO) IN BANJARMASIN - Elvina Hapizah; Fajar Kusuma Dwi Kurniawan; Galuh Dwinta Sari; Diana Wibowo; Ika Kusuma Wardani (FKG ULM, 2024)
Background: Based on the data from Riskesdas (Primary Health Research) of 2013, the prevalence of malocclusion in 12-15 years old in the Province of South Kalimantan was 5.6%, which was the age group with the highest malocclusion over other age groups. Malocclusion itself is a dental abnormality that ranks third after dental caries and periodontal disease in oral health problems in Indonesia with a very high prevalence of around 83.3%. Treatment for malocclusion condition can be performed by orthodontic treatment. One of the indexes for measuring orthodontic treatment needs is IKPO (Orthodontic Treatment Needs Indicator). This indicator is highly suitable to be used as an instrument to find out the orthodontic treatment needs of students, especially in Indonesia. Objective: To find out the level of orthodontic treatment needs in students 12-15 years old using Orthodontic Treatment Needs Indicator (IKPO) according to age and gender. Methods: The study conducted was quantitative descriptive research with a cross-sectional approach. Samples were 108 students of 12-15 years old in 5 Junior High Schools in Banjarmasin. Every sample filled out IKPO questionnaires to asses orthodontic treatment needs. Results: The results of the study showed that 88% of respondents need orthodontic treatment. This consisted of 58 female students and 37 male students. The age group that required the most orthodontic treatment in this study was 12 years old. Conclusion: Orthodontic treatment needs in students 12-15 years old were high in Banjarmasin, which was measured using IKPO.